A New Method for Morphometric Analysis of Opal Phytoliths from Plants. (7th October 2014) - Out, Welmoed A.; Pertusa Grau, José F.; Madella, Marco
Abstract Micro-morphometry has substantially gained ground in the field of phytolith analysis, but the comparability of results is limited due to the use of different methods. This paper presents a new, user-friendly method based on open-source software (FIJI) that is proposed as a step towards the introduction of a standard method. After obtaining a mask of a phytolith by making a digital drawing, 27 commonly used variables of size and shape are measured automatically. This method is not only useful for phytolith analysis, but may also be used for other fields of morphometric research. Users can furthermore customize the software tool when additional variables are required.